Additive manufacturing using recycled polyolefins with olefin block copolymers and articles manufactured therefrom
Patent Information
- Application Number
- JP2022520558
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-11
- Filing Date
- 2020-10-07
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-10-07
Smart Images

Figure 0007652766000003 
Figure 0007652766000004 
Figure 0007652766000005
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Application No. 62 / 913,762, filed October 11, 2019, the entirety of which is incorporated herein by reference.
[0002] The field of the invention is methods of additive manufacturing in which a thermoplastic polymer material (e.g., in the form of pellets, powder, or filaments) is softened by heating (e.g., melting) and extruded, for example, using a filament that is advanced and heated through a nozzle and deposited on a platen (commonly referred to as Fused Filament Modeling or FFF). [Background technology]
[0003] Additive manufacturing of thermoplastic polymers (typically nylon) is well known. For example, fused filament fabrication (FFF), also commonly referred to as plastic jet printing, has been used to form three-dimensional (3D) parts by using thermoplastic filaments that are drawn into a nozzle, heated, melted, and then extruded. The extruded filaments melt together upon cooling (see, for example, U.S. Patent No. 5,121,329). Because this technique requires melting and extrusion of filaments, it has been limited to materials thermoplastic polymers (typically nylon) and complex devices.
[0004] It is hoped to find utility for post-consumer recycled polyolefin (PCRPO) streams, such as post-consumer recycled streams that contain polyolefins, such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), high density polyethylene (HDPE), polyolefins (PP), and / or combinations thereof, as a significant or major or primary component. However, polymers that exhibit crystal formation in specific orientations, such as high density polyethylene (HDPE) or polypropylene, also tend to warp and not print properly during additive manufacturing, such as FFF. These problems can be particularly severe when attempting to form larger parts (e.g., cross-sectional areas greater than 2 square inches). The use of PCRPO streams can also have problems in additive manufacturing due to compositional variations, including the presence of contaminants in the stream. Summary of the Invention
[0005] 1. A method of additive manufacturing comprising: (i) providing a thermoplastic material comprising 5 to 75 weight percent post-consumer recycled polyolefin and 25 to 95 weight percent olefin block copolymer; (ii) heating and expelling the thermoplastic material through a nozzle to form an extrudate that is deposited on a substrate; (iii) moving the substrate, the nozzle, or a combination thereof while dispensing the thermoplastic material such that there is a horizontal displacement between the substrate and the nozzle in a predetermined pattern to form an initial layer of material on the substrate; (iv) repeating steps (ii) and (iii) to form successive layers of adhered material on the initial layer to form the additively manufactured part.
[0006] Also disclosed is an additively manufactured article comprised of at least two layers bonded together, at least one layer comprising 5 to 75 weight percent post-consumer recycled polyolefin and 25 to 95 weight percent olefin block copolymer.
[0007] Also disclosed are filaments useful for additive manufacturing, including filaments comprising multiple layers comprising 5 to 75 weight percent post-consumer recycled polyolefin and 25 to 95 weight percent olefin block copolymer.
[0008] Improved additive manufacturing methods can be used for rapid prototyping of articles. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a side view of an additively manufactured article of the present invention shaped by a method of the present invention. [Diagram 2] FIG. 2 is an end view of an initial layer extrudate formed by the method of the present invention. [Diagram 3] FIG. 2 is an end view of a completed initial layer of the method of the present invention. [Figure 4] 1 is a photograph of an example of an additively manufactured article according to the method of the present invention. [Diagram 5] 1 is a photograph of an example of an additively manufactured article according to the method of the present invention. [Figure 6] Photographs showing what a print test failure looks like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] method The additive manufacturing method can use any suitable equipment and method for heating and extruding a thermoplastic composition into successive layers to build an article. For example, FFF additive manufacturing as known in the art can include the steps of heating, dispensing, repeating, and optionally removing method steps. The method can utilize filaments that have been previously made and then loaded into a known FFF printing device. Alternatively, the filaments can utilize pellets of the thermoplastic composition. Alternatively, the components of the thermoplastic composition can be fed, melt blended, and then extruded. The thermoplastic material can be heated (e.g., at a nozzle) in the equipment to soften (e.g., melt) and extruded as an extrudate in a conventional manner while forming the additive manufacturing as follows.
[0011] 1-3, the method includes heating and discharging a thermoplastic material through a nozzle 100 attached to a nozzle assembly 110. Discharging the material forms an extrudate 120 that forms an initial layer 130 and a continuous layer 140 on a substrate 150. Although the nozzle assembly 110 is depicted as being orthogonal to the substrate, it can be set at any useful angle for forming the extrudate, with the extrudate 120 and nozzle assembly 110 forming an obtuse angle and the extrudate 120 being parallel to the substrate. Additionally, as shown in FIGS. 1-3, the nozzle assembly 110 can be rotated about its longitudinal axis to, for example, reorient the shape of the opening of the nozzle 100 to produce an extrudate 120 having a different relationship to the substrate 150.
[0012] Relative motion between the substrate 150 and the nozzle assembly 110 is also shown, but it is understood that the substrate 150, the nozzle assembly 110, or both can be moved to produce any horizontal or vertical relative motion. The motion is performed in a predetermined manner, which can be accomplished by any known CAD / CAM methods and apparatus, such as those known in the art and readily available robotic or computerized machine tool interfaces. Such patterning is described, for example, in U.S. Patent No. 5,121,329.
[0013] The extrudate 120 may be discharged continuously or may be interrupted to form the initial layer 130 and the successive layer 140. If an interrupted extrudate 120 is desired, the nozzle may be equipped with a valve (not shown) to block the flow of material. Such a valve mechanism may be any suitable one, such as any known electromechanical valve that can be easily controlled by any CAD / CAM method in conjunction with the pattern. The interruptions may create gaps 160, which may remain as gaps or may be filled with the same or different extrudate 120 in a subsequent deposition from the nozzle.
[0014] To improve adhesion, the substrate may have a coating or film of a compatible material, such as polypropylene or polyethylene tape.
[0015] Two or more nozzle assemblies 110 can be used to create composite or gradient structures in an additively manufactured part. Similarly, a second nozzle assembly 110 may be used to dispense a support structure that can be subsequently removed to form more complex geometric structures, as described in U.S. Patent No. 5,503,785. The support material may be any known in the art that adds support and can be easily removed, such as wax.
[0016] Thermoplastic Materials The method uses thermoplastic materials including a post-consumer recycled polyolefin (PCRPO) composition and an olefin block copolymer composition.
[0017] PCRPO Post-consumer recycled polyolefin (PCRPO) compositions are derived from consumer products or containers, or industrial scrap. Sources of PCRPO compositions can include, for example, bottle caps and closures, milk, water or orange juice containers, detergent bottles, office automation equipment (printers, computers, copiers, etc.), white goods (refrigerators, washing machines, etc.), household appliances (televisions, video cassette recorders, stereos, etc.), automobile shredder residue (mixed material remaining after most of the metals are separated from shredded automobiles and other metal-rich products that have been "shredded" by metal recyclers), packaging waste, household waste, rotomolded parts (kayak / cooler), construction waste, industrial molding and extrusion scrap.
[0018] The PCRPO composition comprises at least 50 weight percent, or at least 60 weight percent, or at least 70 weight percent, or at least 75 weight percent, or at least 80 weight percent, or at least 85 weight percent, or at least 90 weight percent, or at least 95 weight percent polyolefin, based on the total weight of the post-consumer recycled polyolefin composition. The PCRPO composition can comprise up to 99.9 weight percent, or up to 99.5 weight percent, or up to 99 weight percent, or up to 98 weight percent, or up to 97 weight percent, or up to 96 weight percent, or up to 95 weight percent, or up to 90 weight percent polyolefin, based on the total weight of the post-consumer recycled polyolefin composition.
[0019] The polyolefin in the PCRPO can be any polyolefin found in recycle streams, such as high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), MDPE, ULDPE, polypropylene (PP), functionalized polyethylene, and combinations of two or more of the foregoing polymers.
[0020] The term "LDPE" may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene", and is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated by reference). LDPE resins typically have a viscosity of 0.916 to 0.935 g / cm. 3 The density is in the range of
[0021] The term "LLDPE" includes both resins made using traditional Ziegler-Natta and chromium-based catalysts, as well as single-site catalysts, including but not limited to bis-metallocene catalysts (sometimes referred to as "m-LLDPE") and constrained geometry catalysts, and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPEs contain less long chain branching than LDPEs and include substantially linear ethylene polymers as further defined in U.S. Pat. Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Pat. No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698, and / or blends thereof (such as those disclosed in U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,854,045). LLDPE can be made by gas phase, liquid phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0022] The term "MDPE" means 0.926 to 0.935 g / cm 3 "MDPE" refers to polyethylene having a density of greater than 2.5. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to bismetallocene catalysts and constrained geometry catalysts, and typically has a molecular weight distribution ("MWD") greater than 2.5.
[0023] The term "HDPE" refers to any polyethylene having a viscosity of about 0.935 g / cm, typically prepared using a single-site catalyst, including, but not limited to, Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts. 3 Super ~ approx. 0.970g / cm 3 It refers to polyethylene having a density of
[0024] The term "ULDPE" generally refers to any polymer with a viscosity of 0.880-0.912 g / cm prepared using a single-site catalyst, including but not limited to Ziegler-Natta, chromium, or bis-metallocene and constrained geometry catalysts. 3 It refers to polyethylene having a density of
[0025] "Polypropylene" refers to a polymer containing more than 50% by weight of units derived from propylene monomers. It includes polypropylene homopolymer or copolymer (meaning units derived from two or more comonomers). Common forms of polypropylene known in the art include homopolymer polypropylene (hPP), random copolymer polypropylene (rcPP), impact copolymer polypropylene (hPP+, at least one elastomeric impact modifier) (ICPP) or high impact polypropylene (HIPP), high melt strength polypropylene (HMS-PP), isotactic polypropylene (iPP), syndiotactic polypropylene (sPP), and combinations thereof.
[0026] A "functionalized polyolefin" is a polyolefin that contains atoms other than carbon and hydrogen, for example, a functionalized polyolefin may be modified with hydroxyl, amine, aldehyde, epoxide, ethoxylate, carboxylic acid, ester, anhydride groups, or combinations thereof. In general, functionalized polyolefins contain functional groups such as protonated (-COOH) or unprotonated (-COO-) acid groups or acid salts, including ethylene / acrylic acid copolymers (e.g., polymers sold under the trade names PRIMACOR™ (SK Global's trademark NUCREL™ (a trademark of The Dow Chemical Company), and ESCOR™ (ESCOR is a trademark of Exxon Corporation)), ethylene / methacrylic acid copolymers (e.g., polymers sold under the trade name NUCREL™), maleic anhydride modified polyolefins (e.g., polymers sold under the trade names LICOCENE™ (a trademark of Clariant AG Corporation), EPOLENE™ (EPOLENE is a trademark of Westlake Chemical Corporation), and MORPRIME™ (a trademark of Rohm and Hass Chemicals LLC)), and those modified with vinyl acetate (ELVAX, Dow Chemical Ethylene ester copolymers such as acrylate modified (ELVALOY available from DuPont), and AMPLIFY (Dow). Similarly, subsequent ionomers of functionalized polyolefins are formed by neutralization with cations from metals such as Zn, Na, Mg, or K, examples being SURLYN available from Dow Chemical Company.
[0027] PCRPO compositions primarily contain contaminants resulting from the article from which they are derived and the use of such articles, examples of such contaminants include non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof.
[0028] The amount of contaminants can be at least 0.1, or 0.5, or at least 1, or at least 2, or at least 3, or at least 4, or at least 5, or at least 10 weight percent. The amount of contaminants can be up to 50, or up to 40, or up to 30, or up to 25, or up to 20, or up to 15, or up to 10, or up to 5 weight percent total contaminants based on total weight or PCRPO composition. Larger amounts of contaminants can occur when the contaminants include other polymeric materials such as, for example, nylon, polyester (e.g., polyethylene terephthalate (PET), alkylene vinyl alcohol (e.g., ethylene vinyl alcohol (EVOH), etc.), etc.
[0029] PCRPO is at least 100, or at least 150, or at least 200 mm 2 / 24.6cm 3 (200 microns). For example, a sample having a gel index of 24.6 cm 3 A unit sample volume of can be inspected for each gel measurement. Inspection can be done using a gel counter with a light source, a line scan camera (e.g., Optical Control Systems (OCS) FSA100 camera (25um resolution)), and an imaging processor. The gel counter can be configured in a transmission mode where film passes between the light source and the camera. Analysis can include illuminating the film sample with the light source. The camera can measure the intensity of the light transmitted through the film. Gel present in the film refracts or blocks the light, reducing the amount of light that reaches the camera. In this way, a digitized image of the gel can be created. The area of the digitized gel can be determined by summing the number of pixels, which includes. The diameter of the gel is assigned by calculating the diameter of a circle with an equivalent area. 24.6 cm 3 The sample volume is 0.323 m for a 76 micron thick film. 2In each measurement, the total area of all gels less than 200 microns in diameter is determined. Fifty such measurements can be performed. The average value of the total gel area is calculated based on the total number of measurements (e.g., 50) and is expressed as mm per volume of the sample examined (e.g., a sample of 24.6 cubic centimeters). 2 The gel index of a virgin polyolefin resin is usually expressed as about 10 mm of the sample. 2 / 24.6cm 3 PCRPO has a higher gel index due to contamination and because the material has been made into an article, used, and recovered. Treated means that the material has previously been through at least two or at least three thermal cycles of heating and cooling.
[0030] The PCRPO may have a melt index (defined below) in accordance with ASTM 1238-13 of at least 0.1, or at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5 g / 10 min, up to 40, or up to 30, or up to 20, or up to 10, or up to 5, or up to 2 g / 10 min, at 190° C. and 2.16 kg.
[0031] Olefin block copolymer. The composition further comprises an olefin block copolymer composition.
[0032] In the broadest sense, an olefin block copolymer is a polymer made using separate catalysts and shuttling agents to form a block copolymer of two different olefin monomers, monomer mixtures, or combinations thereof. The olefin block copolymer formed may have some other polymers in the polymer product made, such as a portion of the homopolymer of the monomers used to make the olefin block copolymer or a mixture of monomers. These methods are known and are described, for example, in U.S. Patent Nos. 8,822,598, 8,686,087, 9,511,567, 8,822,598, and 9,243,090.
[0033] The olefin block copolymer is composed of two or more olefin comonomers. Preferably, the olefin block copolymer comprises, in polymerized form, propylene and ethylene and / or one or more C4-20 α-olefin comonomers.
[0034] The olefin block copolymer composition may include block copolymers in the following composites, referred to herein as Block Composites (BC) and Crystalline Block Composites (CBC).
[0035] For example, "Block Composite" ("BC") is (i) an ethylene-based polymer (EP) having an ethylene content of from 10 mol% to less than 90 mol% (soft copolymer); (ii) an alpha-olefin based polymer (AOP) having an alpha-olefin content of greater than 90 mole % (rigid copolymer); (iii) a block copolymer having an ethylene block (EB) and an alpha-olefin block (AOB), The ethylene block (soft block / soft segment) of the block copolymer is of the same composition as the ethylene-based polymer of component (i) of the block composite, and the alpha-olefin block (hard block / hard segment) of the block copolymer is of the same composition as the alpha-olefin-based polymer of component (ii) of the block composite. The term "same composition" refers to two components having the same monomer and comonomer content, the same structure, and the same physical properties. The compositional division between the amounts of ethylene-based polymer and alpha-olefin-based polymer will be the same or essentially the same as between the corresponding blocks in the block copolymer. Non-limiting examples of suitable α-olefins include C3-C10 α-olefins, such as, for example, C3, C4, C5, C6, and C8 α-olefins. In a particular embodiment, the α-olefin is propylene. In a further embodiment, AOB and EB can be iPP-EP diblock copolymers.
[0036] A "hard" block (also referred to as a hard segment) refers to a highly crystalline block of polymerized units in which the monomer (e.g., propylene) is present in an amount of 90 mol% or more. In other words, the comonomer content (e.g., ethylene content) in the hard block / segment is 10 mol% or less. In some embodiments, the hard segment comprises all or substantially all propylene units (such as an iPP-isotactic polypropylene-copolymer or homopolymer block). On the other hand, a "soft" block / segment refers to an amorphous, substantially amorphous or elastomeric block of polymerized units in which the monomer (e.g., ethylene) is present in an amount of 10 mol% to less than 90 mol%. In other words, the comonomer content (e.g., propylene content) of the soft block / segment is greater than 10 mol%.
[0037] The BC may have a total ethylene content of 25% by weight, or 30% by weight to 50% by weight, or 55% by weight, or 60% by weight, or 70% by weight, based on the total weight of the BC. The remaining portion of the total weight of the BC may be accounted for by units derived from at least one C3 to C10 α-olefin, such as propylene. The BC may be a propylene-based polymer containing 50% by weight or more of units derived from propylene, based on the total weight of the BC.
[0038] The BC can include (i) a soft copolymer having an ethylene content of 10 mol% to less than 90 mol%, (ii) a hard copolymer having a propylene content of 90 mol% or more, and (iii) a block copolymer (e.g., diblock) having a soft block (i.e., soft segment) and a hard block (i.e., hard segment), where the hard block of the block copolymer is of the same composition as the hard copolymer of the block composite, and the soft block of the block copolymer is of the same composition as the soft copolymer of the block composite. The compositional division between the amounts of the soft and hard copolymers will be the same or essentially the same as that between the corresponding blocks in the block copolymer.
[0039] BC can include (i) a soft copolymer having an ethylene content of more than 10% by weight and less than 86% by weight, (ii) a hard copolymer having a propylene content of more than 80% by weight and up to 100% by weight, and (iii) a block copolymer (e.g., diblock) having a soft block (i.e., soft segment) and a hard block (i.e., hard segment), where the hard block of the block copolymer has the same composition as the hard copolymer of BC, and the soft block of the block copolymer has the same composition as the soft copolymer of BC. The compositional division between the amounts of the soft and hard copolymers will be the same or essentially the same as between the corresponding blocks in the block copolymer.
[0040] In BC, the hard block refers to a highly crystalline block of polymerized α-olefin units (e.g., propylene). In the hard block, the monomer (i.e., propylene) may be present in an amount of more than 80% by weight (e.g., more than 85% by weight, more than 90% by weight, and / or more than 95% by weight) based on the weight of the hard block. The remainder of the hard block may be a comonomer (e.g., ethylene) in an amount of less than 20% by weight (e.g., less than 15% by weight, and / or less than 10% by weight) based on the weight of the hard block. In an embodiment, the hard block comprises all or substantially all propylene units, such as an iPP (isotactic) homopolymer block, or an iPP copolymer block containing less than 10% by weight of ethylene. In an exemplary embodiment, the soft block refers to an amorphous, substantially amorphous, or elastomeric block of polymerized ethylene units. In the soft block, the monomer (i.e., ethylene) may be present in an amount of greater than 20% to less than 90% by weight (e.g., 40% to 89%, 45% to 85%, and / or 50% to 80% by weight) based on the weight of the soft block. The remainder of the soft block may be a comonomer (e.g., propylene).
[0041] The block composite can include a block copolymer having 30-70% by weight of a hard block and 30-70% by weight of a soft block, in other words, the block composite can include a block copolymer having 30-70% by weight of a hard block and 30-70% by weight of a soft block, based on the total weight of the block copolymer.
[0042] The BC block copolymers can have the formula (EP)-(iPP), where EP represents the soft block of polymerized ethylene and propylene monomer units (e.g., 50-80% by weight ethylene and the remainder propylene) and iPP represents the hard block of an isotactic propylene homopolymer or copolymer (e.g., less than 10% by weight ethylene and the remainder propylene).
[0043] An exemplary measure of the relative amount of block copolymers is referred to as the Block Composite Index (BCI), as discussed further below. The BCI for BC is greater than 0 and less than 1.0. BC can have a Block Composite Index (BCI) greater than zero, or greater than 0.1, or greater than 0.2, or greater than 0.3 to 0.4, or 0.5, or 0.6, or 0.7, or 0.8, or 0.9, or 1.0. BC can have a BCI greater than 0 to 0.4, or between 0.1 and 0.3, or between 0.4. In another embodiment, BC has a BCI greater than 0.4 to 1.0, or between 0.4, or 0.5, or between 0.6 and 0.7, or 0.9, or 1.0. BC can have a BCI between 0.7, or 0.8, or between 0.9 and 1.0.
[0044] The BC can have a weight average molecular weight (Mw) of 10,000 g / mol, or 35,000 g / mol, or 50,000 g / mol, or 80,000 g / mol to 200,000 g / mol, or 300,000 g / mol, or 500,000 g / mol, or 1,000,000 g / mol, or 2,500,000 g / mol. The molecular weight distribution (Mw / Mn) or polydispersity of the BC can be less than 5, or 1, or 1.5 to 4, or 5.
[0045] The melt flow rate (MFR) of BC can be 0.1 g / 10 min, or 3 g / 10 min to 10 g / 10 min, or 15 g / 10 min, or 20 g / 10 min, or 60 g / 10 min, or 100 g / 10 min, or 1,000 g / 10 min at 230°C and 2.16 kg according to ASTM 1238-13.
[0046] The density of the BC can be 0.850 g / cc, or 0.860 g / cc, or 0.865 g / cc to 0.890 g / cc, or 0.895 g / cc, or 0.900 g / cc, or 0.910 g / cc, or 0.920 g / cc.
[0047] BC can show two melting peaks, a first melting peak (Tm1BC) and a second melting peak (Tm2BC). BC can have a second melting peak (Tm2BC) that is greater than 35°C, greater than 90°C, greater than 100°C, or 40°C, or between 100°C and 150°C.
[0048] The difference between Tm1BC and Tm2BC can be equal to or greater than 40° C. The difference between Tm1BC and Tm2BC can be greater than 40° C., or greater than 50° C., or greater than 60° C.
[0049] BC is based on the total weight of the BC. (i) EP from a lower limit of 0.5%, or 10%, or 20%, or 30% by weight to an upper limit of 40%, or 50%, or 60%, or 70%, or 79%, or 95% by weight; (ii) an AOP having a lower limit of 0.5%, 10%, 20%, or 30% by weight to an upper limit of 40%, 50%, 60%, 70%, 79%, or 95% by weight; (iii) It may contain 5% by weight, or 50% to 99% by weight of a block copolymer.
[0050] The sum of the weight percentages of the EP, AOP, and block copolymer equals 100%.
[0051] The block copolymer of BC can contain ethylene blocks (EB) from a lower limit of 5%, or 10%, or 25%, or 30% to an upper limit of 70%, or 75%, or 90%, or 95% by weight, and alpha-olefin blocks (AOB) from an upper limit of 95%, or 90%, or 75%, or 70% to a lower limit of 30%, or 25%, or 10%, or 5% by weight.
[0052] In an embodiment, the BC is, based on the total weight of the BC, (i) EP from a lower limit of 0.5%, or 10%, or 20%, or 30% by weight to an upper limit of 40%, or 50%, or 60%, or 70%, or 79%, or 95% by weight; (ii) iPP having a lower limit of 0.5% by weight, or 10% by weight, or 20% by weight, or 30% by weight, to an upper limit of 40% by weight, or 50% by weight, or 60% by weight, or 70% by weight, or 79% by weight, or 95% by weight; (iii) comprising, consisting essentially of, or consisting of a block copolymer from a lower limit of 5%, or 10%, or 25%, or 30%, or 50% by weight to an upper limit of 70%, or 80%, or 90%, or 95%, or 99% by weight; The block composite has one, some, or all of the following properties: (a) the EP contains, by weight, ethylene and the inverse amount of propylene from a lower limit of 50%, or 55%, or 60% by weight to an upper limit of 65%, or 70%, or 75%, or 80% by weight, or from a lower limit of 20%, or 25%, or 30%, or 35% by weight to an upper limit of 40%, or 45%, or 50% by weight, based on the total weight of the EP; and / or (b) the EP contains polymerized ethylene units and the inverse amount of polymerized propylene units from a lower limit of 10 mol%, or 20 mol%, or 30 mol%, or 40 mol%, or 50 mol%, or 60 mol%, or 65 mol%, or 70 mol%, or 73 mol% to an upper limit of 75 mol%, or 80 mol%, or 85 mol%, or 89 mol%, based on the total moles of EP, or from a lower limit of 11 mol%, or 15 mol%, or 20 mol%, or 25 mol% to an upper limit of 27 mol%, or 30 mol%, or 35 mol%, or 40 mol%, or 50 mol%, or 60 mol%, or 70 mol%, or 80 mol%, or 90 mol% of polymerized propylene units; and / or (c) the iPP contains propylene and the inverse amount of ethylene from an upper limit of 100%, or 99.5%, or 99% by weight to a lower limit of 95%, or 90%, or 85%, or 80%, or 75%, or 70%, or 65%, 60%, or 55% by weight, or from a lower limit of 0%, or 0.5% by weight to an upper limit of 1%, or 5%, or 10%, or 15%, or 20%, or 25%, or 30%, or 35%, or 40%, or 45% by weight, based on the total weight of the iPP; and / or (d) the iPP contains a lower limit of 90 mol%, or 91 mol%, or 92 mol%, or 93 mol%, or 94 mol%, or 95 mol%, or 96 mol%, or 97 mol%, or 98 mol% to 99 mol% polymerized propylene units and the inverse amount of polymerized ethylene units, or 1 mol% to 2 mol%, or 3 mol%, or 4 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 8 mol%, or 9 mol%, or 10 mol% polymerized ethylene units, based on the total moles of iPP; and / or (e) the block copolymer contains EB of 5%, 10%, 25%, or 30% by weight, or an upper limit of 70%, 75%, 90%, or 95% by weight, or an inverse amount of iPP blocks, or an upper limit of 95%, 90%, 75%, or 70% by weight, or an upper limit of 30%, 25%, 10%, or 5% by weight, based on the total weight of the block copolymer; and / or (f) a BCI of 0.1, or 0.2, or 0.3, or 0.4 to 0.5, or 0.6, or 0.7, or 0.8, or 0.9, or 1.0; and / or (g) a melt flow rate (MFR) in accordance with ASTM 1238-13 of a minimum of 0.1 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 15 g / 10 min, or 18 g / 10 min, to a maximum of 20 g / 10 min, or 30 g / 10 min, or 50 g / 10 min, or 1,000 g / 10 min, at 230° C. and 2.16 kg; and / or (h) a weight average molecular weight (Mw) from a lower limit of 50,000 g / mol, or 80,000 g / mol, or 100,000 g / mol to an upper limit of 150,000 g / mol, or 200,000 g / mol, or 300,000 g / mol, or 500,000 g / mol, or 1,000,000 g / mol; and / or (i) an Mw / Mn of 1.0, or 1.5, or 2.0, or 2.5, or 3.0, or 3.5, or 3.7-3.8, or 4.0, or 4.5, or 5.0; and / or (h) a heat of fusion (or enthalpy of fusion) of 20 joules per gram (J / g), or 25 J / g, or 30 J / g, or 35 J / g, or 50 J / g, or 60 J / g, or 70 J / g, or 75 J / g, or 80 J / g, to an upper limit of 85 J / g, or 90 J / g, or 95 J / g, or 100 J / g, or 125 J / g; and / or (j) a crystallization temperature Tc between a lower limit of 70°C, or 75°C, or 80°C, or 85°C, and an upper limit of 90°C, or 95°C, or 100°C, and / or (k) a first peak Tm1BC with a lower limit of 100°C, or 110°C, or 120°C, or 130°C, or 135°C to an upper limit of 138°C, or 140°C, or 145°C, or 150°C; and / or (l) a second peak Tm2BC between a lower limit of 35°C or 40°C and an upper limit of 45°C, or 50°C, or 60°C; and / or (m) a difference between Tm1BC and Tm2BC that is greater than 40° C., or greater than 50° C., or greater than 60° C.; and / or (n) a total ethylene content from a lower limit of 20%, or 25%, or 30%, or 33% by weight to an upper limit of 35%, or 40%, or 45%, or 50% by weight, based on the total weight of the BC. The BC may have all of the above properties (a) to (n).
[0053] B.C. (i) an ethylene-based polymer having an ethylene content of 10 mol% to less than 90 mol%; (ii) a propylene-based polymer having a propylene content of greater than 90 mol %; (iii) a block copolymer comprising an ethylene block and a propylene block; (iii) the ethylene blocks of the block copolymer have the same composition as the (i) ethylene-based polymer, and (iii) the propylene blocks of the block copolymer have the same composition as the (ii) propylene-based polymer; A BC may have one, some, or all of the following characteristics: (a) a melt flow rate (MFR) in accordance with ASTM 1238-13 of a minimum of 0.1 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 15 g / 10 min, or 18 g / 10 min, to a maximum of 20 g / 10 min, or 30 g / 10 min, or 50 g / 10 min, or 1,000 g / 10 min, at 230° C. and 2.16 kg; and / or (b) exhibits two melting peaks, and / or (C) a first peak Tm1BC with a lower limit of 100°C, or 110°C, or 120°C, or 130°C, or 135°C to an upper limit of 138°C, or 140°C, or 145°C, or 150°C; and / or (d) a second peak Tm2BC at 35°C, or between 40°C and 45°C, or 50°C, or 60°C, and / or (e) A difference between Tm1BC and Tm2BC that is greater than 40° C., or greater than 50° C., or greater than 60° C. BC can have all of the above characteristics (a) to (e).
[0054] The block composite may include two or more of the embodiments discussed herein above.
[0055] The term "Crystalline Block Composite" ("CBC") refers to a material that is made up of three polymer components: (i) a crystalline ethylene-based polymer (CEP) (also referred to herein as a soft polymer of CBC) having an ethylene content of 90 mole % or greater, based on the total moles of polymerized monomer units in the crystalline ethylene-based polymer (CEP); (ii) a crystalline alpha-olefin based polymer (CAOP) (also referred to herein as a hard polymer of CBC) having an alpha-olefin content of greater than 90 mole percent, based on the total moles of polymerized monomer units in the crystalline alpha-olefin based polymer (CAOP); (iii) a block copolymer comprising a crystalline ethylene block (CEB) and a crystalline alpha-olefin block (CAOB), The crystalline ethylene block has a Tm that is the same or similar to that of the crystalline ethylene-based polymer (CEP) of component (i); The crystalline alpha-olefin block has the same or similar Tm as the crystalline alpha-olefin-based polymer (CAOP) of component (ii); The phrase "same or similar" refers to an absolute Tm difference of ≦5°C, or ≦4°C, or ≦3°C, or ≦2°C.
[0056] "Crystalline Block Composites" ("CBCs") are (i) a crystalline ethylene-based polymer (CEP) (also referred to herein as a soft polymer) having an ethylene content of 90 mole % or greater; (ii) a crystalline alpha-olefin based polymer (CAOP) (also referred to herein as a hard polymer) having an alpha-olefin content of greater than 90 mole %; (iii) a block copolymer comprising a crystalline ethylene block (CEB) and a crystalline alpha-olefin block (CAOB), The crystalline ethylene block (CEB) (soft block / soft segment) of the block copolymer is of the same composition as the crystalline ethylene-based polymer (CEP) of component (i) of the block composite, and the crystalline alpha-olefin block (CAOB) (hard block / hard segment) of the block copolymer is of the same composition as the crystalline alpha-olefin-based polymer (CAOP) of component (ii) of the block composite. The compositional division between the amounts of CEP and CAOP will be the same or essentially the same as that between the corresponding blocks in the block copolymer. When produced in a continuous process, the CBC has a polydispersity index (PDI) of 1.7, or 1.8 to 3.5, or 5, or 10, or 15. Such CBCs are described, for example, in U.S. Patent Application Publication Nos. 2011 / 0313106, 2011 / 0313108, and 2011 / 0313108, all published on December 22, 2011, and PCT Publication No. WO2014 / 043522(A1), published on March 20, 2014, each of which is incorporated by reference herein for its description of CBCs, processes for making CBCs, and methods for analyzing CBCs. Non-limiting examples of suitable α-olefins include C3-C10 α-olefins, such as, for example, C3, C4, C5, C6, and C8 α-olefins. In certain embodiments, the α-olefin is propylene.
[0057] A "crystalline ethylene-based polymer" ("CEP") contains at least 90 mol% polymerized ethylene units with any comonomer content of 10 mol% or less, or from 0 mol% to 5 mol%, or 7 mol%, or 10 mol%. A crystalline ethylene-based polymer has a corresponding melting point of 75°C or greater, or 90°C or greater, or 100°C or greater.
[0058] A "crystalline alpha-olefin-based polymer" ("CAOP") is a highly crystalline polymer containing polymerized α-olefin units, where the monomer (e.g., propylene) is present in an amount of more than 90 mol%, more than 93 mol%, or more than 95 mol%, or more than 98 mol%, based on the total weight of the crystalline α-olefin-based polymer (propylene). In an embodiment, the polymerized α-olefin units are polypropylene. The comonomer (e.g., ethylene) content in the CAOP is less than 10 mol%, or less than 7 mol%, or less than 5 mol%, or less than 2 mol%. CAOPs of propylene crystallinity have corresponding melting points of 80° C. or more, or 100° C. or more, or 115° C. or more, or 120° C. or more. In an embodiment, the CAOP comprises all or substantially all propylene units.
[0059] Non-limiting examples of other suitable α-olefin units (in addition to propylene) that can be used in the CAOP are those containing 4 to 10 carbon atoms, such as 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. Non-limiting examples of suitable diolefins are isoprene, butadiene, 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,7-octadiene, 1,9-decadiene, dicyclopentadiene, methylene-norbornene, 5-ethylidene-2-norbornene, and the like, or combinations containing at least one of the foregoing α-olefin units.
[0060] The block copolymer of CBC contains a crystalline ethylene block (CEB) and a crystalline alpha-olefin block (CAOB). In the crystalline ethylene block (CEB), the ethylene monomer is present in an amount of more than 90 mol%, or more than 93 mol%, or more than 95 mol%, or more than 90 mol%, based on the total moles of CEB. In an embodiment, the crystalline ethylene block (CEB) polymer is polyethylene. The polyethylene is present in an amount of more than 90 mol%, or more than 93 mol%, or more than 95 mol%, based on the total moles of CEB. If any comonomer is present in the CEB, it is present in an amount of less than 10 mol%, or less than 5 mol%, based on the total moles of CEB.
[0061] CAOB comprises polypropylene blocks copolymerized with other α-olefin units containing 4 to 10 carbon atoms. Non-limiting examples of suitable α-olefins are provided above. Polypropylene is present in CAOB in an amount of 90 mol% or more, or greater than 93 mol%, or greater than 95 mol%, based on the total moles of CAOB. The comonomer content in CAOB is less than 10 mol%, or less than 7 mol%, or less than 5 mol percent, based on the total moles in CAOB. CAOB of propylene crystallinity have corresponding melting points of 80°C or more, or 100°C or more, or 115°C or more, or 120°C or more. In an embodiment, CAOB comprises all or substantially all propylene units.
[0062] The CBC may contain propylene, 1-butene, or 4-methyl-1-pentene, and one or more comonomers. The CBC may contain, in polymerized form, propylene and ethylene, and / or one or more C4-20 α-olefin comonomers, and / or one or more additional copolymerizable comonomers, or the CBC contains 4-methyl-1-pentene and ethylene, and / or one or more C4-20 α-olefin comonomers, or the CBC contains 1-butene and ethylene, propylene, and / or one or more C5-C20 α-olefin comonomers, and / or one or more additional copolymerizable comonomers. Additional suitable comonomers are selected from diolefins, cyclic olefins, and cyclic diolefins, halogenated vinyl compounds, and vinylidene aromatic compounds. The monomer may be propylene and the comonomer may be ethylene.
[0063] The CBC can be a propylene-based polymer that contains 50% or more by weight of units derived from propylene, based on the total weight of the CBC.
[0064] Comonomer content in CBC can be measured using any suitable technique, such as techniques based on nuclear magnetic resonance (NMR) spectroscopy.
[0065] The CBC may exhibit two melting peaks, a first melting peak (Tm1CBC) and a second melting peak (Tm2CBC). The CBC may have a second melting peak (Tm2CBC) that is greater than 100°C, or greater than 120°C, or greater than 125°C. In an embodiment, the CBC has a second melting peak (Tm2CBC) of 100°C, or 120°C, or 125°C to 220°C, or 250°C.
[0066] The difference between Tm1CBC and Tm2CBC may be equal to or greater than 40° C. The difference between Tm1CBC and Tm2CBC may be greater than 40° C., or greater than 50° C., or greater than 60° C.
[0067] The CBC can have a melt flow rate (MFR) of 0.1 g / 10 min to 30 g / 10 min, or 50 g / 10 min, or 1,000 g / 10 min at 230° C. and 2.16 kg in accordance with ASTM 1238-13.
[0068] The CBC can have a weight average molecular weight (Mw) from a lower limit of 10,000 g / mol, or 35,000 g / mol, or 50,000 g / mol to an upper limit of 200,000 g / mol, or 300,000 g / mol, or 1,000,000 g / mol, or 2,500,000 g / mol.
[0069] The CBC may have a Crystalline Block Composite Index (CBCI) greater than zero, or greater than 0.1, or greater than 0.2, or greater than 0.3 to 0.4, or 0.5, or 0.6, or 0.7, or 0.8, or 0.9, or 1.0. The CBC may have a CBCI greater than 0.4 to 1.0, or 0.4, or 0.5, or 0.6 to 0.7, or 0.9, or 1.0. The CBC may have a CBCI of 0.7, or 0.8, or 0.9 to 1.0.
[0070] The CBC can contain, based on the total weight of the crystalline block composite, (i) 0.5% to 79%, or 95% by weight of CEP, (ii) 0.5% to 79%, or 95% by weight of CAOP, and (iii) 5%, or 50% to 99% by weight of block copolymer.
[0071] The sum of the weight percentages of CEP, CAOP, and the block copolymer equals 100%.
[0072] The block copolymer of CBC can contain a crystalline ethylene block (CEB) from a lower limit of 5%, or 10%, or 25%, or 30% to an upper limit of 70%, or 75%, or 90%, or 95% by weight, and a crystalline alpha-olefin block (CAOB) from an upper limit of 95%, or 90%, or 75%, or 70% to a lower limit of 30%, or 25%, or 10%, or 5% by weight.
[0073] The CBC can contain (i) a crystalline ethylene / propylene copolymer (CEP), CEP; (ii) a CAOP, an isotactic crystalline propylene homopolymer (iPP); and (iii) a block copolymer containing an iPP block (CAOB) and an EP block (CEB), wherein the block copolymer comprises a diblock of formula (2): (CEP)-(iPP) Formula (2).
[0074] CBC is based on the total weight of CBC. (i) CEP having a lower limit of 0.5 wt%, or 10 wt%, or 20 wt%, or 30 wt% to an upper limit of 40 wt%, or 50 wt%, or 60 wt%, or 70 wt%, or 79 wt%, or 95 wt%, (ii) iPP having a lower limit of 0.5% by weight, or 10% by weight, or 20% by weight, or 30% by weight, to an upper limit of 40% by weight, or 50% by weight, or 60% by weight, or 70% by weight, or 79% by weight, or 95% by weight; (iii) comprising, consisting essentially of, or consisting of a block copolymer from a lower limit of 5%, or 10%, or 25%, or 30%, or 50% by weight to an upper limit of 70%, or 80%, or 90%, or 95%, or 99% by weight; The crystalline block composite material has one, some, or all of the following properties: (a) the CEP contains, by weight, 85%, or 89% to 92%, or 95%, or 99% ethylene and the inverse amount of propylene, or 1%, or 5%, or 8% to 11%, or 15% propylene, based on the total weight of the CEP; and / or (b) the CEP contains, based on the total moles of CEP, 90 mol%, or 91 mol%, or 92 mol% to 95 mol%, or 96 mol%, or 97 mol%, or 98 mol%, or 99 mol% polymerized ethylene units and the inverse amount of polymerized propylene units, or 1 mol%, or 2 mol%, or 3 mol%, or 4 mol%, or 5 mol% to 8 mol%, or 9 mol%, or 10 mol% polymerized propylene units; and / or (c) the iPP contains propylene and the inverse amount of ethylene from an upper limit of 100%, or 99.5%, or 99% by weight to a lower limit of 95%, or 90%, or 85%, or 80%, or 75%, or 70%, or 65%, 60%, or 55% by weight, or from a lower limit of 0%, or 0.5% by weight to an upper limit of 1%, or 5%, or 10%, or 15%, or 20%, or 25%, or 30%, or 35%, or 40%, or 45% by weight, based on the total weight of the iPP; and / or (d) the iPP contains polymerized propylene units with a lower limit of 90 mol%, or 91 mol%, or 92 mol%, or 93 mol%, or 94 mol%, or 95 mol%, or 96 mol%, or 97 mol%, or 98 mol% to 99 mol% polymerized ethylene units, or an upper limit of 1 mol% to 2 mol%, or 3 mol%, or 4 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 8 mol%, or 9 mol%, or 10 mol% polymerized ethylene units, based on the total moles of iPP; and / or (e) the block copolymer contains EB and the inverse amount of iPP blocks from a lower limit of 5 wt.%, or 10 wt.%, or 25 wt.%, or 30 wt.% to an upper limit of 50 wt.%, or 70 wt.%, or 75 wt.%, or 90 wt.%, or 95 wt.%, or from an upper limit of 95 wt.%, or 90 wt.%, or 75 wt.%, or 70 wt.%, or 50 wt.%, or from a lower limit of 30 wt.%, or 25 wt.%, or 10 wt.%, or 5 wt.%, based on the total weight of the block copolymer; and / or (f) a CBCI with a lower limit of 0.1, or 0.2, or 0.3, or 0.4, or 0.5, or 0.6, and an upper limit of 0.7, or 0.8, or 0.9, or 1.0; and / or (g) a melt flow rate (MFR) at 230°C and 2.16 kg of 0.1 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 15 g / 10 min, or 20 g / 10 min, or a lower limit of 23 g / 10 min to 40 g / 10 min, or 50 g / 10 min, or an upper limit of 1,000 g / 10 min, in accordance with ASTM 1238-13; and / or (h) a weight average molecular weight (Mw) from a lower limit of 50,000 g / mol, or 70,000 g / mol, or 80,000 g / mol, or 100,000 g / mol to an upper limit of 130,000 g / mol, or 150,000 g / mol, or 200,000 g / mol, or 300,000 g / mol, or 500,000 g / mol, or 1,000,000 g / mol; and / or (i) an Mw / Mn ratio between a lower limit of 1.0, or 1.5, or 2.0, or 2.5, or 3.0, or 3.5, or 3.7, or 3.8, or 4.0, and an upper limit of 4.3, or 4.5, or 5.0; and / or (j) a heat of fusion (or enthalpy of fusion) from a lower limit of 20 J / g, or 25 J / g, or 30 J / g, or 35 J / g, or 50 J / g, or 60 J / g, or 70 J / g, or 75 J / g, or 80 J / g, or 85 J / g, or 90 J / g, or 92 J / g to an upper limit of 100 J / g, or 110 J / g, or 115 J / g, or 125 J / g; and / or (k) a crystallization temperature Tc of 70°C, or 75°C, or 80°C, or 85°C, or 90°C to 95°C, or 100°C, and / or (l) a first peak Tm1CBC with a lower limit of 100°C, or 110°C, or 120°C, or 130°C, to an upper limit of 136°C, or 140°C, or 145°C, or 150°C, and / or (m) a second peak Tm2CBC with a lower limit of 90°C, or 95°C, or 100°C, or 103°C, to an upper limit of 105°C, or 110°C, or 115°C, or 120°C, or 125°C, or 130°C, or 140°C, or 150°C; and / or (n) a difference between Tm1CBC and Tm2CBC that is greater than 40° C., or greater than 50° C., or greater than 60° C.; and / or (o) a total ethylene content of 20%, or 25%, or 28% to 47%, or 50%, or 55%, or 60%, or 70% by weight, based on the total weight of the CBC. The CBC can have all of the above properties (a) through (o).
[0075] Crystalline block composites are (i) a crystalline ethylene-based polymer having an ethylene content of greater than 90 mol %; (ii) a crystalline propylene-based polymer having a propylene content of greater than 90 mol %; (iii) a block copolymer comprising a crystalline ethylene block and a crystalline propylene block; (iii) the crystalline ethylene block of the block copolymer has the same composition as (i) the crystalline ethylene-based polymer, and (iii) the crystalline propylene block of the block copolymer has the same composition as (ii) the crystalline propylene-based polymer; A CBC has one, some, or all of the following properties: (a) a melt flow rate (MFR) in accordance with ASTM 1238-13 of a minimum of 0.1 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 15 g / 10 min, or 18 g / 10 min, to a maximum of 20 g / 10 min, or 30 g / 10 min, or 50 g / 10 min, or 1,000 g / 10 min, at 230° C. and 2.16 kg; and / or (b) exhibits two melting peaks, and / or (c) a first peak Tm1CBC between a lower limit of 100°C, or 100°C, or 110°C, or 120°C, or 130°C, and an upper limit of 136°C, or 140°C, or 145°C, or 150°C; and / or (d) a second peak Tm2CBC with a lower limit of 90°C, or 95°C, or 100°C, or 103°C, to an upper limit of 105°C, or 110°C, or 115°C, or 120°C, or 125°C, or 130°C, or 140°C, or 150°C; and / or (e) A difference between Tm1CBC and Tm2CBC that is greater than 40° C., or greater than 50° C., or greater than 60° C. In a further embodiment, the CBC has all of the above characteristics (a)-(e).
[0076] A crystalline block composite material may include two or more of the variations discussed herein.
[0077] It is understood that the sum of each of the components of the polymers disclosed herein, including the aforementioned BC and CBC polymers, equals 100 mole %.
[0078] The preferred BC is one that is composed of polymerized propylene. Desirably, the PP block copolymer is one that is composed of an isotactic polypropylene (iPP)-based block and an EP copolymer-based block. The block segment composition can range from about 10 to 90 weight percent or preferably 30 to 70 weight percent EP block and corresponding 90 to 10 weight percent or preferably 70 to 30 weight percent iPP block, the EP block being at least about 60%, 80% to about 90 weight percent ethylene on average overall, the remainder being propylene. It is understood that the ethylene and propylene referred to in the blocks refer to their residues after incorporation into the polymer. Such PP block copolymers are available from The Dow Chemical Company (Midland, MI) under the trademark INTUNE.
[0079] Additional Codification The thermoplastic material may further include certain optional additional components such as pigments, fillers (e.g., glass beads, talc, calcium carbonate, carbon fiber, glass fiber), lubricants, slip agents, or flame retardants. The amount of all such optional additional components combined is preferably less than 30 weight percent, or less than 20 weight percent, or less than 10 weight percent, or less than 5 weight percent, based on the total weight of the thermoplastic material. If used, the additional optional additional components may be present from 0.1 weight percent or 1 weight percent, based on the total weight of the thermoplastic material. Any of the additional components may be individually present in an amount of 0.1, or 1 weight percent to less than 25, or less than 20, or less than 15, or less than 10, or less than 5 weight percent, based on the total weight of the thermoplastic material. In particular, the composition may have an amount of fibrous fillers fibrous fillers and inorganic fillers (separately and combined) less than 25, or less than 20, or less than 15, or less than 10, or less than 5 weight percent. Lubricants such as silicone fluids, or polymer processing aids such as fluoropolymers (eg, 3M Dynamar™ Polymer Processing Additives) may be present in amounts less than 2%, less than 1%, or less than 0.1%.
[0080] Goods The article made by the above method comprises at least two layers bonded together, at least one layer comprises a thermoplastic material as described herein. The article can comprise multiple layers, at least a portion of the layers comprises a thermoplastic material as described herein. The article can comprise multiple layers, all layers comprise a thermoplastic material as described herein. The article can comprise multiple layers or thermoplastic materials as described herein and a support layer of another polymer that can be removed, such as those known in the art, including wax and cellulose-based polymers.
[0081] Test Method Melt flow rate (MFR) can be measured according to ASTM D-1238-13 (230° C., 2.16 kg). Results are reported in grams / 10 minutes. Melt index (MI) can be measured according to ASTM D-1238-13 (190° C., 2.16 kg). Results are reported in grams / 10 minutes.
[0082] Differential Scanning Calorimetry (DSC) Differential scanning calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide range of temperatures. For example, a TA Instruments Q1000 DSC equipped with an RCS (refrigerated cooling system) and an autosampler was used to perform this analysis. A nitrogen purge gas flow rate of 50 ml / min was used during testing. Each sample was melt pressed into a thin film at approximately 190°C, and the molten sample was then air-cooled to room temperature (approximately 25°C). A 3-10 mg, 6 mm diameter specimen was removed from the cooled polymer, weighed, placed in a light aluminum pan (50 mg), and crimped shut. Analysis was then performed to determine its thermal properties.
[0083] The thermal behavior of the sample was determined by ramping the temperature of the sample up and down to generate a heat flow vs. temperature profile. To remove the thermal history, the sample was first rapidly heated to 180°C and held isothermally for 3 minutes. The sample was then cooled to -80°C at a cooling rate of 10°C / min and held isothermally at -80°C for 3 minutes. The sample was then heated to 180°C (this is the "second heat" ramp) at a heating rate of 10°C / min. The cooling curve and the second heat curve were recorded. The determined value was the extrapolated melting onset T m and the extrapolated crystallization onset T c The heat of fusion (H f ) (also known as enthalpy of fusion) and peak melting temperature were reported from the second heating curve. The melting point T was determined by first subtracting the baseline between the beginning and end of the melting transition. mwas determined from the DSC heating curve. A tangent line was then drawn to the data on the low temperature side of the melting peak. Where this line intersects the baseline is the extrapolated melting onset (T m ) as explained in Bernhard Wunderlich, The Basis of Thermal Analysis, Thermal Characterization of Polymeric Materials 92, 277-278 (Edith A. Turi ed., 2d ed. 1997). The melting point is the peak temperature.
[0084] 13 C nuclear magnetic resonance (NMR) Sample preparation: Samples were prepared by adding approximately 2.6 g of a 50 / 50 mixture of tetrachloroethane-d2 / orthodichlorobenzene that was 0.025 M in chromium acetylacetonate (relaxation agent) to 0.21 g of sample in a 10 mm NMR tube. The sample was dissolved and homogenized by heating the tube and its contents to 135°C-140°C.
[0085] Data Acquisition Parameters: Data was collected using a Bruker 400MHz spectrometer equipped with a Bruker Dual DUL high temperature CryoProbe. Data was acquired using 320 transients per data file, a pulse repetition delay of 7.3 seconds (6 seconds delay + 1.3 seconds acquisition time), a flip angle of 90 degrees, and inverse gated decoupling at a sample temperature of 120°C. All measurements were performed on non-spinning samples in a stationary fashion. Samples were homogenized immediately prior to insertion into a heated (125°C) NMR sample exchanger and thermally equilibrated in the probe for 7 minutes prior to data acquisition. Acquisition was performed using a spectroscopic width of 25000Hz and a file size of 65K data points. NMR is used, for example, to determine the total weight percent of ethylene in the whole polymer, the weight percent of ethylene in the xylene soluble fraction, for the crystalline block composite index or block composite index, as discussed below.
[0086] Gel Permeation Chromatography (GPC) for Molecular Weight The molecular weights and molecular weight distributions described herein can be determined by GPC calibrated against polystyrene standards. High temperature gel permeation chromatography (GPC) systems such as units from Agilent Technology and PolymerChar (Valencia, Spain) were used. The concentration detector was an infrared detector (IR-5) from Polymer Char Inc. Data collection was performed using GPCOne (PolymerChar). The carrier solvent was 1,2,4-trichlorobenzene (TCB). The system was equipped with an online solvent degassing device from Agilent. The column section was operated at 150° C. The columns were four Mixed A LS 30 cm, 20 micron columns. The solvent was nitrogen purged TCB containing approximately 200 ppm 2,6-di-t-butyl-4-methylphenol (BHT). The flow rate was 1.0 mL / min and the injection volume was 200 μl. A sample concentration of 2 mg / mL was prepared by dissolving the sample in N2-purged and preheated TCB (containing 200 ppm BHT) at 160° C. for 2.5 hours with gentle stirring.
[0087] The GPC column set-up was calibrated by using 20 narrow molecular weight distribution polystyrene standards. The molecular weights (MW) of the standards ranged from 580 g / mol to 8,400,000 g / mol, and the standards were contained in six "cocktail" mixtures. Each standard mixture had at least one order of magnitude between the individual molecular weights. The equivalent polypropylene molecular weight of each PS standard was calculated using the following equations, along with the reported Mark-Houwink coefficients for polypropylene (Th. G. Scholte, NL J Meijerink, HM Schoffeleers, & AMG Brands, J. Appl. Polym. Sci., 29, 3763-3782 (1984)) and polystyrene (EP Totocka, RJ Roe, NY Hellman, & PM Muglia, Macromolecules, 4, 507 (1971)):
[0088] High Temperature Liquid Chromatography (HTLC) High temperature liquid chromatography (HTLC) experimental method instrumentation was performed according to the published method of D. Lee et al., J. Chromatogr. A 2011, 1218, 7173. Two Shimadzu (Columbia, MD, USA) LC-20AD pumps were used to deliver decane and trichlorobenzene (TCB), respectively. Each pump was connected to a 10:1 fixed flow splitter (part number: 620-PO20-HS, Analytical Scientific Instruments Inc., CA, USA). The splitter had a pressure drop of 1500 psi (10.34 MPa) at 0.1 mL / min in H2O according to the manufacturer. The flow rate of both pumps was set at 0.115 mL / min. After splitting, the flow rate was 0.01 mL / min for both decane and TCB, as determined by weighing the collected solvent for more than 30 min. The volume of the collected eluate was determined by the mass and density of the solvent at room temperature. A small stream was delivered to the HTLC column and separated. The main stream was sent back to the solvent reservoir. A 50-μL mixer (Shimadzu) was connected after the splitter to mix the solvents from the Shimadzu pumps. The mixed solvent was then delivered to the injector in the oven of a Waters (Milford, MA, USA) GPCV2000. A Hypercarb™ column (2.1×100 mm, 5 μm particle size) was connected between the injector and a 10-port VICI valve (Houston, TX, USA). The valve was equipped with two 60-μL sample loops. This valve was used for sequential sample elution from the first dimension (D1) HTLC column to the second dimension (D2) SEC column. A Waters GPCV2000 pump and a PLgel Rapid™-M column (10×100 mm, 5 μm particle size) were connected to a VICI valve of a D2 size-exclusion chromatography (SEC). A symmetrical configuration was used for the connections as described in Y. Brun & P. Foster, J. Sep. Sci. 2010, 33, 3501.A dual angle light scattering detector (PD2040, Agilent, Santa Clara, Calif., USA) and an IR5 infrared absorption detector were connected after the SEC column to measure the concentration, composition and molecular weight.
[0089] Separation for HTLC: Approximately 30 mg was dissolved in 8 mL of decane by gently shaking the vial at 160° C. for 2 hours. The decane contained 400 ppm of BHT (2,6-di-tert-butyl-4-methylphenol) as a radical scavenger. The sample vial was then transferred to the autosampler of the GPCV2000 for injection. The temperatures of the autosampler, injector, both Hypercarb and PLgel columns, the 10-port VICI valve, and both the LS and IR5 detectors were maintained at 140° C. throughout the separation.
[0090] The initial conditions before injection were as follows: the flow rate of the HTLC column was 0.01 mL / min; the solvent composition of the D1 Hypercarb column was 100% decane; the flow rate of the SEC column was 2.51 mL / min at room temperature; the solvent composition of the D2 PLgel column was 100% TCB; the solvent composition of the D2 SEC column did not change throughout the separation.
[0091] A 311-μL aliquot of the sample solution was injected onto the HTLC column, which induced the gradient described below. 0-10 min, 100% decane / 0% TCB, From 10 min to 651 min, TCB increased linearly from 0% TCB to 80% TCB.
[0092] The injection also triggered the collection of light scattering signals at a 15° angle (LS15) using an EZChrom™ chromatography data system (Agilent), as well as the “measure” and “methyl” signals from the IR5 detector (IR measure and IR methyl). The analog signals from the detector were converted to digital signals via an SS420X analog-to-digital converter. The collection frequency was 10 Hz. The injection also triggered the switching of a 10-port VICI valve. The valve switch was controlled by a relay signal from the SS420X converter. The valve was switched every 3 minutes. Chromatograms were collected from 0 to 651 minutes. Each chromatogram consisted of 651 / 3=217 SEC chromatograms.
[0093] After the gradient separation, 0.2 mL of TCB and 0.3 mL of decane were used to wash and re-equilibrate the HTLC column for the next separation. The flow rate for this step was 0.2 mL / min and was delivered by a Shimadzu LC-20 AB pump connected to a mixer. EXAMPLES
[0094] material: PCRPO: Avangard Natura™ 150PCR (collected from flexible packaging waste streams that often contain large amounts of LDPE (melting point: 108°C (density 0.922-0.94 grams per cubic centimeter (g / cc) by differential scanning calorimetry (DSC), melt flow index (MI) 0.8145 g / 10 min by ASTM D1238, ash content 1.85)) ENVISION ECOPRIME™ HDPE rich stream with gel index (200 micron) 296.2, melting point 133°C by DSC, density 0.9657 g / cc, MI 0.764 g / 10 min.
[0095] Olefin Block Copolymer The block copolymer CBC1 is used having the following characteristics: [Table 1] · wt% PP - the weight percent of propylene polymers in the CBC or BC as determined by HTLC separation as described above. Mw - weight average molecular weight of CBC or BC in Kg / mol determined by GPC as above. · Mw / Mn - molecular weight distribution of CBC or BC determined by GPC as above. · Total wt% Weight percent of ethylene in CBC or BC determined by C2-NMR, the remainder being propylene. · Tm (℃) Peak 1 (Peak 2) - Peak melting temperature determined by the second heating curve from DSC. Peak 1 refers to the melting of CEB / CEP (in case of CBC) or EB / EP (in case of BC), and Peak 2 refers to the melting of CEB or CEP. · Tc (℃) - Peak crystallization temperature determined by DSC cooling scan.
[0096] Block copolymers can be prepared by a process comprising contacting an addition polymerizable monomer or mixture of monomers under addition polymerization conditions with a composition comprising at least one addition polymerization catalyst, at least one cocatalyst, and a chain shuttling agent, characterized in that at least some of the growing polymer chains are formed under different process conditions in two or more reactors operated under steady-state polymerization conditions, or in two or more zones of a reactor operated under plug-flow polymerization conditions. The term "shuttling agent" refers to a compound or mixture of compounds capable of causing polymer exchange between at least two active catalyst sites under polymerization conditions. That is, transfer of polymer fragments occurs both to and from one or more of the active catalyst sites. In contrast to a shuttling agent, a "chain transfer agent" causes the termination of polymer chain growth, corresponding to a single transfer of growing polymer from the catalyst to the transfer agent. In a preferred embodiment, the crystalline block composite comprises a fraction of block polymers having the most probable distribution of block lengths.
[0097] Suitable processes useful for the production of CBC1 can be found, for example, in US Patent Application Publication No. 2008 / 0269412, published October 30, 2008. In particular, it is desirable to carry out the polymerization as a continuous polymerization, preferably a continuous solution polymerization, in which the catalyst components, monomers, and optionally solvents, adjuvants, scavengers, and polymerization aids are continuously fed to one or more reactors or sections, from which the polymer product is continuously removed. As used in this context, within the scope of the terms "continuous" and "continuously" are those processes in which there is intermittent addition of reactants and removal of products at regular or irregular small intervals, such that over time, the overall process is substantially continuous. The chain shuttling agent can be added at any point during the polymerization, including at the outlet of the first reactor or section, or shortly before the outlet of the first reactor, or between the first reactor or section and the second or any subsequent reactor or section. Due to differences in monomers, temperature, pressure, or other polymerization conditions between at least two of the series-connected reactors or zones, polymer segments of different composition, such as comonomer content, crystallinity, density, stereoregularity, regioregularity, or other chemical or physical differences within the same molecule, are formed in the different reactors or zones. The size of each segment or block is determined by the sequential polymer reaction conditions, and preferably results in the most probable polymer size distribution.
[0098] When producing a block polymer with a crystalline ethylene block (CEB) and a crystalline alpha-olefin block (CAOB) in two reactors or zones, it is possible to produce the CEB in the first reactor or zone and the CAOB in the second reactor or zone, or the CAOB in the first reactor or zone and the CEB in the second reactor or zone. It may be more advantageous to produce the CEB in the first reactor or zone with the addition of fresh chain shuttling agent. The increased level of ethylene present in the reactor or zone producing the CEB may result in a much higher molecular weight in that reactor or zone than in the zone or reactor producing the CAOB. The fresh chain shuttling agent reduces the MW of the polymer in the reactor or zone producing the CEB, thus resulting in an overall better balance in length between the CEB and CAOB segments.
[0099] When reactors or zones are operated in series, it is necessary to maintain diverse reaction conditions so that one reactor produces CEB and the other produces CAOB. Carryover of ethylene from the first reactor to the second reactor (in series) or from the second reactor to the first reactor through the solvent and monomer recycle system is preferably minimized. There are many possible unit operations to remove this ethylene, but because ethylene is more volatile than the higher alpha olefins, one simple method is to remove most of the unreacted ethylene by a vaporization step by reducing the pressure of the effluent of the reactor producing the CEB and flashing off the ethylene. An exemplary approach is to avoid additional unit operations and take advantage of the much greater reactivity of ethylene relative to the higher alpha olefins so that the conversion of ethylene across the CEB reactor approaches 100%. By maintaining the alpha olefin conversion at a high level (90-95%), the overall conversion of monomer across the reactors can be controlled.
[0100] Exemplary catalysts and catalyst precursors for use in forming crystalline block composite materials include, for example, metal complexes as disclosed in International Publication No. WO2005 / 090426. Other exemplary catalysts are also disclosed in U.S. Patent Application Publication Nos. 2006 / 0199930, 2007 / 0167578, and 2008 / 0311812, U.S. Patent No. 7,355,089, and International Publication No. WO2009 / 012215.
[0101] Optionally, the crystalline block composite material (CBC1) may be characterized by differential scanning calorimetry (DSC), C13 nuclear magnetic resonance (NMR), gel permeation chromatography (GPC), and high temperature liquid chromatography (HTLC) fractionation, as described in more detail in U.S. Patent Application Publication Nos. US2011 / 0082257, US2011 / 0082258, and US2011 / 0082249, all published April 7, 2011, which are incorporated herein by reference for their description of analytical methods.
[0102] procedure Compounding is carried out by standard methods known in the art using a JSW twin screw extruder at 135°C.
[0103] The filament was formed by standard methods known in the art using a Noztek Pro filament extruder. Briefly, the pellets were fed into a desktop single screw extruder. The extruder was heated to 140° C. and the screw was rotated at 15 revolutions per minute (RPM). The polymer melt was extruded through a 1.75 mm nozzle to produce a filament that could be fed into a 3D printer.
[0104] 3D Printing: Parts were printed on a Hyrel System 30M commercially available from Hyrel 3D, Norcross, Georgia (USA). Small 3D hexagonal prisms (dimensions 1.5cmx5mm or 1.5cmx5cm, layer height 0.2mm, 100% linear infill) were printed. The printer bed temperature was 95°C and the nozzle temperature ranged from 180 to 240°C.
[0105] The compositions are prepared by compounding (only when two materials are used), made into filaments, and then printed as above with various amounts of OBC and PCRPO, as shown in Table 1. Samples with 20 weight percent OBC or less either failed to extrude or failed to print. Sample 1 printed successfully and is shown in Figure 4. Sample 4 printed successfully into an article and is shown in Figure 5. Figure 6 shows an example of a material that could be extruded but could not be successfully printed due to extreme warping during printing, i.e., no further successive layers could be added. [Table 2]
[0106] The present disclosure includes the following aspects:
[0107] Embodiment 1. A method of additive manufacturing to form an additively manufactured article, comprising: (i) providing a thermoplastic material comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants. (ii) heating and discharging the thermoplastic material through a nozzle to form an extrudate deposited on a substrate; (iii) moving the substrate, the nozzle, or a combination thereof while discharging the thermoplastic material such that there is a horizontal displacement between the substrate and the nozzle in a predetermined pattern to form an initial layer of material on the substrate; (iv) repeating steps (ii) and (iii) to form subsequent layers of material adhered to the initial layer; and (v) optionally repeating steps (ii) and (iii) to form additional subsequent layers adhered to the previously formed subsequent layers. Aspect 2. The post-consumer recycled polyolefin is at least 100 mm 2 / 24.6cm 3 2. The method of embodiment 1, wherein the gel is characterized by a gel index (200 microns) of 0.01 to 0.15.
[0023] Aspect 3. The method of any one of the preceding aspects, wherein the polyolefin in the post-consumer recycled polyolefin composition is selected from high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, functionalized polyolefins, and combinations of two or more of the foregoing polymers.
[0023] Embodiment 4. The method of any one of the preceding embodiments, wherein the contaminants in the post-consumer recycled polyolefin composition are selected from non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof.
[0023] Aspect 5. The method of any one of the preceding aspects, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition.
[0023] Embodiment 6. The method of any one of the preceding embodiments, wherein the olefin block copolymer composition comprises a block composite, a crystalline block composite, or a blend having a block olefin copolymer therein, the block olefin copolymer comprising an isotactic polypropylene block and a polyethylene rich block. Embodiment 7. The method of embodiment 6, wherein the isotactic polypropylene blocks are 10 mol % to 90 mol %, preferably 30 mol % to 70 mol %, of the olefin block copolymer, with the remaining balance being polyethylene rich blocks.
[0023] Embodiment 8. The method of embodiment 6 or 7, wherein the polyethylene rich blocks comprise on average at least 60 mole %, preferably at least 70 mole %, ethylene, based on the total moles of the polyethylene rich blocks, with the remainder being propylene.
[0108]
[0023] Aspect 9. The method of any one of aspects 6 to 8, wherein the block composite or crystalline block composite has a block composite index, as measured by nuclear magnetic resonance (NMR) spectroscopy, of 0.1 to 0.9, preferably 0.2 to 0.8.
[0023] Embodiment 10. The method of any one of the preceding embodiments, wherein the thermoplastic material comprises less than 20 weight percent, preferably less than 5 weight percent, of fibrous filler and inorganic material.
[0023] Aspect 11. The method of any one of the preceding aspects, wherein the additively manufactured article is a prototype.
[0023] Embodiment 12. The method of any one of the preceding embodiments, wherein the thermoplastic material is formed into filaments that are drawn into and melted within the nozzle. Embodiment 13. An article made by the method of any one of the preceding embodiments. Embodiment 14. An additively manufactured article comprised of at least two layers adhered to one another, at least one layer being comprised of a thermoplastic material comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, the post-consumer recycled polyolefin composition comprising at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants.
[0023] Embodiment 15. The article of embodiment 14, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition.
[0031] Example 16. The article of example 14 or 15, wherein the thermoplastic material comprises less than 20 weight percent, preferably less than 5 weight percent, of fibrous fillers and inorganic materials. Example 17. The article of any one of Examples 14-16, which is a prototype. Aspect 18: The post-consumer recycled polyolefin has a thickness of at least 100 mm 2 / 24.6cm 3 18. The article of any one of claims 14-17, characterized by a Gel Index (200 microns). Aspect 19: The article of any one of aspects 14 to 18, wherein the polyolefin in the post-consumer recycled polyolefin composition is selected from high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, functionalized polyolefins, and combinations of two or more of the foregoing polymers. Aspect 20: The article of any one of aspects 14 to 19, wherein the contaminants in the post-consumer recycled polyolefin composition are selected from non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof.
[0041] Embodiment 21: The article of any one of embodiments 14-20, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition. Example 22: The article of any one of Examples 14 to 21, wherein the olefin block copolymer composition comprises a block composite, a crystalline block composite, or a blend having a block olefin copolymer therein, the block olefin copolymer comprising an isotactic polypropylene block and a polyethylene-rich block.
[0041] Example 23: The article of example 22, wherein the isotactic polypropylene blocks are 10 mol% to 90 mol%, preferably 30 mol% to 70 mol% of the olefin block copolymer, with the remaining balance being polyethylene rich blocks.
[0031] Embodiment 23. The article of embodiment 21 or 22, wherein the polyethylene rich blocks comprise on average at least 60 mol%, preferably at least 70 mol%, ethylene, based on the total moles of the polyethylene rich blocks, with the remainder being propylene.
[0036] Example 24. The article of any one of Examples 21-23, wherein the block composite or crystalline block composite has a Block Composite Index, as measured by Nuclear Magnetic Resonance (NMR) spectroscopy, of 0.1 to 0.9, preferably 0.2 to 0.8.
[0036] Embodiment 25. The article of any one of embodiments 14-24, wherein the thermoplastic material comprises less than 20 weight percent, preferably less than 5 weight percent, of fibrous filler and inorganic materials. Embodiment 26. A filament useful for additive manufacturing, comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants.
[0036] Example 27. The filament of example 26, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition.
[0046] Example 28. The filament of example 26 or 27, comprising less than 20 weight percent, preferably less than 5 weight percent, of fibrous filler and inorganic material. Aspect 29: The post-consumer recycled polyolefin has a thickness of at least 100 mm 2 / 24.6cm 3 29. The filament of any one of embodiments 26-28, characterized by a gel index (200 microns).
[0036] Example 30. The filament of any one of examples 26-29, wherein the polyolefin in the post-consumer recycled polyolefin composition is selected from high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, functionalized polyolefins, and combinations of two or more of the foregoing polymers. Aspect 31: A filament described in any one of aspects 26 to 30, wherein the contaminants in the post-consumer recycled polyolefin composition are selected from non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof.
[0041] Embodiment 32: The filament of any one of embodiments 26-31, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition. Example 33: The filament of any one of Examples 26 to 32, wherein the olefin block copolymer composition comprises a block composite, a crystalline block composite, or a blend having a block olefin copolymer therein, the block olefin copolymer comprising an isotactic polypropylene block and a polyethylene-rich block.
[0036] Example 34. The filament of example 33, wherein the isotactic polypropylene blocks are 10 mol% to 90 mol%, preferably 30 mol% to 70 mol% of the olefin block copolymer, with the remaining balance being polyethylene rich blocks.
[0036] Embodiment 35. The filament of embodiment 33 or 34, wherein the polyethylene rich blocks contain an average of at least 60 mol%, preferably at least 70 mol%, ethylene, based on the total moles of the polyethylene rich blocks, with the remainder being propylene.
[0036] Example 36. The filament of any one of Examples 33 to 35, wherein the block composite or crystalline block composite has a block composite index, as measured by nuclear magnetic resonance (NMR) spectroscopy, of 0.1 to 0.9, preferably 0.2 to 0.8. Embodiment 37: The filament of any one of embodiments 26 to 36, wherein the thermoplastic material contains less than 20 weight percent, preferably less than 5 weight percent, of fibrous filler and inorganic material.
[0109] The compositions, methods, and articles may alternatively comprise, consist of, or consist essentially of any suitable material, step, or ingredient disclosed herein. The compositions, methods, and articles may additionally or alternatively be formulated so as to be free, or substantially free, of any material (or species), step, or ingredient that is not necessary to achieve the function or purpose of the compositions, methods, and articles.
[0110] All ranges disclosed herein are inclusive of the endpoints, and the endpoints are independently combinable with each other (e.g., the range "up to 25 wt.%, more specifically, 5 wt.% to 20 wt.%" includes the endpoints of the range, such as "5 wt.% to 25 wt.%, and all intermediate values). Additionally, the lower and upper limits provided can be freely combined to provide a range. For example, at least 1, or at least 2, or at least 3, and up to 10, or up to 8, or up to 5 can be combined to provide 1 to 10, or 1 to 8, or 1 to 5, or 2 to 10, or 2 to 8, or 2 to 5, or 3 to 10, or 3 to 8, or 3 to 5. A "combination" includes blends, mixtures, alloys, reaction products, and the like. Terms such as "first," "second," and the like are used to distinguish one element from another rather than to denote order, quantity, or importance. The terms "a" and "an" and "the" should be construed to encompass both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. "Or" means "and / or" unless otherwise indicated. References throughout this specification to "some embodiments," "embodiments," and the like mean that a particular element described in connection with an embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various embodiments. "Combinations thereof" are open-ended and include any combination that includes at least one of the recited components or features, optionally with similar or equivalent components or features that are not recited.
[0111] Unless otherwise stated herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, as of the filing date of the earliest priority application in which the test standards are listed. (Aspect) (Aspect 1) 1. A method of additive manufacturing for forming an additively manufactured article, comprising: (I) providing a thermoplastic material comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants; (ii) heating and expelling the thermoplastic material through a nozzle to form an extrudate that is deposited on a substrate; (iii) moving the substrate, the nozzle, or a combination thereof while ejecting the thermoplastic material such that there is a horizontal displacement between the substrate and the nozzle in a predetermined pattern to form an initial layer of the material on the substrate; and (iv) repeating steps (ii) and (iii) to form a subsequent layer of said material adhered onto said initial layer; and (v) optionally repeating steps (ii) and (iii) to form an additional subsequent layer adhered to the previously formed subsequent layer. (Aspect 2) The post-consumer recycled polyolefin has a thickness of at least 100 mm 2 / 24.6cm 3 2. The method of embodiment 1, wherein the gel is characterized by a gel index (200 microns) of 0.01 to 0.15. (Aspect 3) The method of any one of the preceding aspects, wherein the polyolefin in the post-consumer recycled polyolefin composition is selected from high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, functionalized polyolefins, and combinations of two or more of the foregoing polymers. (Aspect 4) 4. The method of any one of the preceding aspects, wherein the contaminants in the post-consumer recycled polyolefin composition are selected from non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof. (Aspect 5) The method of any one of the preceding aspects, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition. (Aspect 6) 4. The method of any one of the preceding aspects, wherein the olefin block copolymer composition comprises a block composite, a crystalline block composite, or a blend having a block olefin copolymer therein, the block olefin copolymer comprising an isotactic polypropylene block and a polyethylene rich block. (Aspect 7) 7. The method of claim 6, wherein the isotactic polypropylene block is 10 mol % to 90 mol %, preferably 30 mol % to 70 mol %, of the olefin block copolymer, with the remaining remainder being the polyethylene-rich block. (Aspect 8) 8. The method of claim 6 or 7, wherein the polyethylene rich blocks contain on average at least 60 mol %, preferably at least 70 mol %, ethylene, based on the total moles of the polyethylene rich blocks, with the remainder being propylene. (Aspect 9) 9. The method of any one of aspects 6 to 8, wherein the block composite or the crystalline block composite has a block composite index, as measured by nuclear magnetic resonance (NMR) spectroscopy, of 0.1 to 0.9, preferably 0.2 to 0.8. (Aspect 10) The method of any one of the preceding aspects, wherein the thermoplastic material comprises less than 20 weight percent, preferably less than 5 weight percent, of fibrous filler and inorganic material. (Aspect 11) 13. The method of any one of the preceding aspects, wherein the additively manufactured article is a prototype. (Aspect 12) 13. The method of any one of the preceding aspects, wherein the thermoplastic material is formed into filaments that are drawn into the nozzle and melted within the nozzle. (Aspect 13) 1. An additively manufactured article comprised of at least two layers bonded together, at least one layer being comprised of a thermoplastic material comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants. (Aspect 14) 1. A filament useful for additive manufacturing, comprising 5 to 75 weight percent, preferably 20 to 60 weight percent, of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of thermoplastic material, said post-consumer recycled polyolefin composition comprising at least 50 weight percent, preferably at least 75 weight percent, more preferably at least 90 weight percent polyolefin, and at least 0.1 weight percent, preferably at least 0.5 weight percent, more preferably at least 1 weight percent contaminants.
Claims
1. 1. A method of additive manufacturing for forming an additively manufactured article, comprising: (i) providing a thermoplastic material comprising 5 to 75 weight percent of a post-consumer recycled polyolefin composition and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent polyolefin and at least 0.1 weight percent contaminants; (ii) heating and expelling the thermoplastic material through a nozzle to form an extrudate deposited on a substrate; (iii) moving the substrate, the nozzle, or a combination thereof while ejecting the thermoplastic material such that there is a horizontal displacement between the substrate and the nozzle in a predetermined pattern to form an initial layer of the material on the substrate; (iv) repeating steps (ii) and (iii) to form a subsequent layer of said material adhered onto said initial layer; and Contains or (i) providing a thermoplastic material comprising 5 to 75 weight percent of a post-consumer recycled polyolefin composition and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, wherein the post-consumer recycled polyolefin composition comprises at least 50 weight percent polyolefin and at least 0.1 weight percent contaminants; (ii) heating and expelling the thermoplastic material through a nozzle to form an extrudate deposited on a substrate; (iii) moving the substrate, the nozzle, or a combination thereof while ejecting the thermoplastic material such that there is a horizontal displacement between the substrate and the nozzle in a predetermined pattern to form an initial layer of the material on the substrate; (iv) repeating steps (ii) and (iii) to form a subsequent layer of said material adhered onto said initial layer; and (v) repeating steps (ii) and (iii) to form an additional subsequent layer adhered to the previously formed subsequent layer.
2. The post-consumer recycled polyolefin composition has a fiber length of at least 100 mm 2 / 24.6cm 3 2. The method of claim 1, characterized by a gel index of 0.1 to 0.5 at 200 microns.
3. 3. The method of any one of claims 1 to 2, wherein the polyolefin in the post-consumer recycled polyolefin composition is selected from high density polyethylene, low density polyethylene, linear low density polyethylene, polypropylene, functionalized polyolefins, and combinations of two or more of the foregoing polymers.
4. 4. The method of any one of claims 1 to 3, wherein the contaminants in the post-consumer recycled polyolefin composition are selected from non-olefin polymers, oxidized polyolefins, inorganic materials, adhesive materials, paper, oil residues, food residues, and combinations of two or more thereof.
5. The method of any one of claims 1 to 4, wherein the amount of contaminants is less than 5 weight percent of the post-consumer recycled polyolefin composition.
6. 6. The method of any one of claims 1 to 5, wherein the olefin block copolymer composition comprises a block composite, a crystalline block composite, or a blend having a block olefin copolymer therein, the block olefin copolymer comprising an isotactic polypropylene block and a polyethylene rich block.
7. 7. The method of claim 6, wherein the isotactic polypropylene block is from 10 mol % to 90 mol % of the olefin block copolymer, with the remaining balance being the polyethylene rich block.
8. 8. The method of claim 6 or 7, wherein the polyethylene rich blocks contain, on average, at least 60 mole percent ethylene, the remainder being propylene, based on the total moles of the polyethylene rich blocks.
9. The method according to any one of claims 6 to 8, wherein the block composite or the crystalline block composite has a block composite index, measured by Nuclear Magnetic Resonance (NMR) spectroscopy, of 0.1 to 0.
9.
10. The method of any one of claims 1 to 9, wherein the thermoplastic material comprises less than 20 percent by weight of fibrous filler and inorganic material.
11. The method of any one of claims 1 to 10, wherein the additively manufactured article is a prototype.
12. A method according to any one of the preceding claims, wherein the thermoplastic material is formed into filaments which are drawn into and melted within the nozzle.
13. The method of any one of claims 1 to 12, wherein the post-consumer recycled polyolefin composition comprises at least 80 weight percent polyolefin.
14. 1. An additively manufactured article comprised of at least two layers adhered to one another, at least one layer being comprised of a thermoplastic material comprising 5 to 75 weight percent of a post-consumer recycled polyolefin composition, and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of the thermoplastic material, the post-consumer recycled polyolefin composition comprising at least 50 weight percent polyolefin, and at least 0.1 weight percent contaminants.
15. 1. A filament useful for additive manufacturing, comprising 5 to 75 weight percent of a post-consumer recycled polyolefin composition and 25 to 95 weight percent of an olefin block copolymer composition, based on a total weight of thermoplastic material, said post-consumer recycled polyolefin composition comprising at least 50 weight percent polyolefin and at least 0.1 weight percent contaminants.
Citation Information
Patent Citations
Polyolefin blend containing polyoctene with compatibilizer
JP2018526501A
Composition of 3D printing filament and filament for 3D manfacturing method thereof
KR101912919B1
Method of additive manufacturing using high performance polyolefins
WO2019133518A1